PENGARUH KEBIJAKAN HUTANG TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN FOOD AND BEVERAGE BURSA EFEK INDONESIA - Ketut Susanta; Ibnu Hajar; Wahyuni Rahmah (STIE ENAM ENAM KENDARI, 2022)
This reaearch is a qualitative research that aims to determine: 1. The effect of debt policy (DAR and DER) on the financial performance of the IDX Food and Beverage company; 2. The effect of DAR on the financial performance of IDX Food and Beverage companies; 3. The effect of DER on the financial performance of IDX Food and Beverage companies. Food and Beverages companies are one of the sectors of manufacturing companies that continue to experience growth over time.The results of this study indicate that debt policy as measured by the debt to asset ratio and debt to equity ratio simultaneously has a positive and significant effect on the financial performance of food and beverage companies on the IDX. This shows that the use of proportional debt will further improve the company's financial performance; Debt to asset ratio has a negative and significant effect on the financial performance of food and beverage companies on the IDX. This shows that the lower the company's DAR ratio, the more it will improve the company's financial performance; Debt to equity ratio has a positive and insignificant effect on the financial performance of food and beverage companies on the IDX. This shows that the better the company's DER ratio, the more the company's financial performance will improve but not significantly.